If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3x + 4) = 4(6x + -4) Reorder the terms: 5(4 + 3x) = 4(6x + -4) (4 * 5 + 3x * 5) = 4(6x + -4) (20 + 15x) = 4(6x + -4) Reorder the terms: 20 + 15x = 4(-4 + 6x) 20 + 15x = (-4 * 4 + 6x * 4) 20 + 15x = (-16 + 24x) Solving 20 + 15x = -16 + 24x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24x' to each side of the equation. 20 + 15x + -24x = -16 + 24x + -24x Combine like terms: 15x + -24x = -9x 20 + -9x = -16 + 24x + -24x Combine like terms: 24x + -24x = 0 20 + -9x = -16 + 0 20 + -9x = -16 Add '-20' to each side of the equation. 20 + -20 + -9x = -16 + -20 Combine like terms: 20 + -20 = 0 0 + -9x = -16 + -20 -9x = -16 + -20 Combine like terms: -16 + -20 = -36 -9x = -36 Divide each side by '-9'. x = 4 Simplifying x = 4
| 2(3b-4)=2(n+3) | | -x+169=281 | | 3/8=24c | | 4a-5+2a+9=21 | | 9-3x+12=15 | | 3(x+4)=6(x-10) | | 51=y+7 | | 264-x=182 | | 6+12n-5=5n+46-2n | | y=4x^2+25x-21 | | 1.2x+-4y=28 | | 3x+4=10x-6 | | 18/x-4=10/x | | X/7+1=-1 | | 1/3x+y=6 | | X-a+4=ax+2b-6 | | 1/2(4a+10)=2+ | | 9=5x-4x+5 | | 4ab+9=c | | -1.5(a+1)=0.5(a-9) | | -1.5(a+1)=0.5(a-9) | | 2/3*8=51/3 | | Y=2(-1/3)+7 | | v-2/2=4/3 | | -3.2=[8p] | | -4a/9-6=4 | | -3(16+3)+4(24+1)=43 | | 1/3t-4/3=-5/4t-3/2 | | 12/5=4w | | 2/3*8 | | 2(a+4)/2=14 | | 3x-27=14 |